HALP AND YOU GET CANDY THE PICTURE BELOW IS YOUR KEY TO CANDY (BRAINLIST)
savblue07 avatar

Answers

Answer 1
Answer:

Answer:

3 1/8

Step-by-step explanation:

Wheres my candy!!

Answer 2
Answer:

Answer:

3 1/8

Step-by-step explanation:

10 - 6 7/8 = 3 + 1/8


Related Questions

The top of a molehill is 4in above ground level.The bottom of a mole’s burrow is -9in relative to ground level. What is the distance between the top of the molehill and the burrow? Show your work.
the temperature at 6pm was 72 degrees. this was 8 degrees cooler than at 4pm. the temperature at 10am wss 5 degrees hotter than at 4pm. what was the temperature 10am
Why can't you use the product of powers rule to simplifythis expression? Explain.3^4.2^8
Find the sum of the two polynomials (2x7−5x6−7x5+8)+(9x7−2x6−2x5−7)
The line AB has midpoint (2,5).A has coordinates (1, 2).Find the coordinates of B.

What are the zeroes of f(x) = y2 - 2x - 3?

Answers

Answer:

Step-by-step explanation:

Product = -3

Sum = -2

Factors = -3 , 1

y² - 2y - 3 = y² + y - 3y - 3

               = y( y + 1) - 3(y + 1)

               = (y +1) (y - 3)

Answer:

x=y^2/2 - 3/2

Step-by-step explanation:

If m∠1 = 3x, m∠3 = 2x + 20 and m∠5 = 30, what is the value of x?

Answers

m∠2 = 180 - m∠1 = 180 - 3x   [supplementary angles]

In a triangle, the three interior angles always add to 180° ⇒
m∠2 + m∠3 + m∠5 = 180
180-3x + 2x+20 + 30 = 180
230 - x = 180
x = 230 - 180
x = 50

Identify the roots of gx= x2+3x-4 x^2-4x+29

Answers

Answer:

x1=1

x2= -4

x3= (2 + 5i)

x4= (2 - 5i)

Step-by-step explanation:

STEP 1-

Find the roots of the first term.

(x^2 + 3x -4)=0

Then group the terms that contain the same variable, and move the constant to the opposite side of the equation.

(x^2 + 3x)=4

Complete the square. Remember to balance the equation by adding the same constants to each side.

(x^2 + 3x + 1.5^2)=4 + 1.5^2

(x^2 + 3x + 1.5^2)=6.25

Rewrite as perfect squares

(x + 1.5)^2=6.25

Square root both sides.

(x + 1.5) = (+/-)2.5

x= -1.5(+/-)2.5

x= -1.5 + 2.5 = 1

x= -1.5 + 2.5= -4

so the factored form of the first term.

(x^2 + 3x + 4) = (x - 1) (x + 4)

STEP 2-

Find the roots of the second term

(x^2 - 4x + 29)= 0

Group terms that contain the same variable, and move the constant to the opposite side of the equation

(x^2 - 4x)= -29

Complete the square. Remember to balance the equation by adding the same constants to each side

(x^2 - 4x + 4) = - 29 + 4

(x^2 -4x + 4) = -25

Rewrite as perfect squares

(x - 2)^2 = -25

Remember that

i = square root of -1

Square root both sides

(x - 2) = (+/-)5i

x= 2 (+/-)5i

x= 2 + 5i

x= 2 - 5i

so the factored form of the second term is

(x^2 - 4x + 29) = (x - (2 + 5i))(x - (2 - 5i))

STEP 3-

Substitute the factored form of the first and second term in g(x)

g(x) = (x-1)(x + 4)(x- (2+ 5i))(x- ( 2-5i)

there for you have your answers

Least number by which 1375 is divided to get a perfect sqaure

Answers

Answer:

55

Step-by-step explanation:

1375 = 5 * 5 * 5 * 11 \n  =  {5}^(2)  * 55 \n

Here 5 is squared and 55 is not.

Hence, the answer is 55

Let F = sin ( 8 x + 5 z ) i − 8 y e x z k . F=sin⁡(8x+5z)i−8yexzk. Calculate div ( F ) div(F) and curl ( F ) . and curl(F). (Express numbers in exact form. Use symbolic notation and fractions where needed.)

Answers

Answer:

Required results are \nabla .\vec{F}=8\cos(8x+5z)-8ye^x[/tex]  and  \nabla* \vec{F}=-8e^xz\uvec{i}+(8ye^xz+5\sin(8x+5z))\uvec{j}

Step-by-step explanation:

Given vector function is,

\vec{F}=\sin(8x+5z)\uvec{i}-8ye^xz\uvec{k}

To find\nabla .\vec{F} and \nabla * \vec{F} .

\nabla .\vec{F}

=((\partial)/(\partial x)\uvec{i}+(\partial)/(\partial y) \uvec{j}+(\partial)/(\partial z) \uvec{k})(\sin(8x+5z)\uvec{i}-8ye^xz\uvec{k})

=(\partial)/(\partial x)(\sin(8x+5z))-(\partial)/(\partial z)(8ye^xz)

=8\cos(8x+5z)-8ye^x

And,

\nabla * \vec{F}

=((\partial)/(\partial x)\uvec{i}+(\partial)/(\partial y) \uvec{j}+(\partial)/(\partial z) \uvec{k})*(\sin(8x+5z)\uvec{i}-8ye^xz\uvec{k})

\end{Vmatrix}

=\uvec{i}\Big[(\partial)/(\partial y)(-8ye^xz)\Big]-\uvec{j}\Big[(\partial)/(\partial x)(-8ye^xz)-(\partial)/(\partial z)(\sin(8x+5z))\Big]+\uvec{k}\Big[-(\partial)/(\partial y)(-\sin(8x+5z))\Big]

=-8e^xz\uvec{i}+(8ye^xz+5\sin(8x+5z))\uvec{j}

Hence the result.

Which is bigger 17 qt or 4 gal

Answers

The bigger quantity out of the given amounts is required.

17 qt is bigger than 4 gal.

Units

The given amounts are 17 qt and 4 gal

Let us convert quarts to gallons so that we can compare the same units.

The conversion factor is

1\ \text{qt}=(1)/(4)\ \text{gal}

For 17 qt

17\ \text{qt}=(17)/(4)=4.25\ \text{gal}

So, the quantities are 4.25 gal and 4 gal.

4.25 gal is greater than 4 gal.

Learn more about units:

brainly.com/question/4158962

~Hello there!
~1 gallon is 4 quarts. 
~4 gallons is 16 quarts.
~So, 17 quarts would be bigger than 4 gallons. 
~I hoped this helped and have a great day!

Other Questions